Analisis Kapabilitas Elastic Endpoint Security Berdasarkan Kerangka Cyber Kill Chain untuk Penguatan Pertahanan Endpoint Pemerintah - Fatikho Kautsar (The Indonesian Journal of Computer Science, 2025)
Cyber threats targeting government institutions continue to escalate in sophistication and operational structure. The 2021 BSSN Cybersecurity Monitoring Report identified web defacement and data breaches as the most prevalent incidents across government entities. The 2024 cybersecurity landscape further reinforces this trend, recording 330,527,636 malicious traffic anomalies nationwide and highlighting ransomware, illegal access, and data breaches as the top incident categories. These developments underscore the persistent exploitation of endpoint weaknesses, emphasizing the need for defense strategies grounded in adversarial attack-chain understanding. This study evaluates the detection capabilities of Elastic Endpoint Security as an Endpoint Detection and Response (EDR) solution through the Cyber Kill Chain (CKC) framework to enhance endpoint defense within government environments. Two realistic attack scenarios were executed to assess detection performance across CKC phases. The findings indicate that Elastic EDR effectively disrupts critical stages, particularly delivery, exploitation, and installation, while providing protective responses aligned with modern defense requirements. This study highlights the viability of open EDR solutions as adaptive, cost-effective defensive foundations for public-sector cybersecurity.